2022
DOI: 10.3390/ijms23063407
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-3 as a Novel Biomarker in Alzheimer’s Disease

Abstract: Early diagnosis of Alzheimer’s disease (AD) is of paramount importance in preserving the patient’s mental and physical health in a fairly manageable condition for a longer period. Reliable AD detection requires novel biomarkers indicating central nervous system (CNS) degeneration in the periphery. Members of the syndecan family of transmembrane proteoglycans are emerging new targets in inflammatory and neurodegenerative disorders. Reviewing the growing scientific evidence on the involvement of syndecans in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 86 publications
(121 reference statements)
0
7
0
Order By: Relevance
“…However, this has been proposed as a compensatory mechanism in response to autogenic syndecan-3 depletion or functional alteration, since syndecan-1 and syndecan-3 have redundant features [ 19 ]. Interestingly, syndecan-3 is implicated in the pathology of Alzheimer’s disease [ 25 ], but no relationship to ALS has been reported yet. It is important to remark that the reanalysis of the potential pathogenic gene variants from a previous ALS study confirmed the absence of pathogenic variants of Piezo2 and Piezo1 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this has been proposed as a compensatory mechanism in response to autogenic syndecan-3 depletion or functional alteration, since syndecan-1 and syndecan-3 have redundant features [ 19 ]. Interestingly, syndecan-3 is implicated in the pathology of Alzheimer’s disease [ 25 ], but no relationship to ALS has been reported yet. It is important to remark that the reanalysis of the potential pathogenic gene variants from a previous ALS study confirmed the absence of pathogenic variants of Piezo2 and Piezo1 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the therapeutic application of AAV9 and the development of novel, CNS-specific AAV serotypes are hindered by the limited knowledge of AAV9 receptors, especially those on the BBB. To explore the potential AAV9 receptors on the BBB, we examined AAV9’s entry into hCMEC/D3 cells, a human BBB model cell line with moderate SDC4 expression [ 62 , 63 ]. Efficient SDC4 knockdown significantly reduced AAV9-mediated gene delivery in AAV9-treated (4 × 10 4 vg/cell at 37 °C for 72 h) hCMEC/D3 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Both syndecans and glypicans have been shown to transport chemokines across peripheral vascular beds (39). The function of syndecans and glypicans as transcytotic transporters of the BBB is underexplored, however a few studies have reported expression of syndecans 2-4 in brain endothelial cells, whereas glypicans are expressed at lower levels or absent (40)(41)(42). Both human and mouse RNAseq datasets of brain microvessels did not detect syndecan-1 (40), which is thought to predominate in the peripheral vasculature, or glypican-2.…”
Section: Discussionmentioning
confidence: 99%